AN ASYMPTOTIC ESTIMATE OF THE NUMBER OF SOLUTIONS OF A SPECIAL SYSTEM OF BOOLEAN EQUATIONS - Yeghiazaryan, Ed.V.; Tonoyan, G.P. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In this paper a special class of systems of Boolean equations is investigated. For a “typical” case of such systems an asymptotic estimate for the number of solutions is determined.